Bioinorganic chemistry a practical course - Metzler-Nolte, Nils (Walter de Gruyter, 2009)
This book presents a unique introduction into the field of bioinorganic chemistry through practical laboratory experiments. Topics include many aspects of modern bioinorganic chemistry such as model systems for metalloenzymes, biosensors, metal bioconjugates and metal-based drugs. Each chapter contains a brief introduction, followed by detailed experimental procedures, completed with all necessary background information for the student as well as their instructors. A valuable supplement to standard textbooks of inorganic and bioinorganic chemistry Essential for all instructors teaching laborat.